Subject disciplines and the construction of teachers’ identities - Thompson, I (Springer, 2023)
This chapter addresses the question of teacher identity by focusing on the role that teachers’ identification with their subject disciplines plays in the formation of teachers’ identities. The chapter takes the starting point that teachers share a common pedagogical and moral imperative to teach children and young people about the subject that they have invested a considerable amount of time to learn themselves. All teachers, whether subject specialists or not, need to learn to acquire an ability to both understand the concepts that matter in a particular subject and the rules of evidence that are accepted within that discipline. It is the contention in this chapter that this conceptual understanding of what it means to teach a particular discipline in particular contexts that is central to the sociocultural identities of teachers. Although the chapter is concerned with the multiple subjects in schools and the identities of teachers of these subjects, it draws on examples from beginning teachers of English in particular as a subject as way of drawing attention to the contested nature of subject disciplines, school subjects, and subject teacher identity.